2013
DOI: 10.1353/hpn.2013.0116
|View full text |Cite
|
Sign up to set email alerts
|

Tense or Aspect?: A Review of Initial Past Tense Marking and Task Conditions for Beginning Classroom Learners of Spanish

Abstract: This essay contributes to the research on the emergence of tense/aspect morphology by reviewing the results and task conditions of studies supporting either the Aspect Hypothesis (AH) or the Default Past Tense Hypothesis (DPTH) for second language (L2) learners of Spanish. The AH has found that past marking emerges based on inherent aspectual categories (Andersen 1991; Andersen and Shirai 1994), and the DPTH proposes (Salaberry 1999, 2002, 2003, 2008; Salaberry and Ayoun 2005) that beginning learners of Spanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Reviews of existing studies (see e.g. Bonilla, 2013;Comajoan, 2005;Shirai, 2004) show that a high number of studies, in particular those investigating the acquisition of lexical aspect, have relied on oral, (semi-)spontaneous data elicited mainly through one task, typically an impersonal narrative. Domínguez et al (2009) and Tracy-Ventura and show that the types of oral tasks most commonly used in studies testing leading hypotheses are personal narratives, impersonal narratives based on pictures or short video clips, role-plays, interviews and free conversations.…”
Section: Choosing the Right Methodology For Investigating Aspect In Amentioning
confidence: 99%
“…Reviews of existing studies (see e.g. Bonilla, 2013;Comajoan, 2005;Shirai, 2004) show that a high number of studies, in particular those investigating the acquisition of lexical aspect, have relied on oral, (semi-)spontaneous data elicited mainly through one task, typically an impersonal narrative. Domínguez et al (2009) and Tracy-Ventura and show that the types of oral tasks most commonly used in studies testing leading hypotheses are personal narratives, impersonal narratives based on pictures or short video clips, role-plays, interviews and free conversations.…”
Section: Choosing the Right Methodology For Investigating Aspect In Amentioning
confidence: 99%
“…In fact, some authors (e.g., Bonilla 2013, Shirai 2004 found that support for the AH was linked to the tasks used. In Bonilla's (2013) survey of studies on L2 Spanish, she found that open-ended tasks better supported the AH, whereas Shirai's (2004) survey of L2 English studies demonstrated that studies which used paper and pencil tests, such as cloze-tests or fill-in-the-blank, supported the AH more consistently. The following section will look at this issue in more detail.…”
Section: Grammatical and Lexical Aspectmentioning
confidence: 99%
“…Although several researchers (e.g., Bonilla 2013, Shirai 2004, Sugaya & Shirai 2007 have made reference to the role of task type in explaining differential outcomes in research testing the AH, few studies have empirically tested this claim. In a study comparing accuracy rates across tasks in L2 Spanish, Salaberry & Lopez-Ortega (1998) found that only the lower proficiency group's use of past tense morphology varied between a written narrative and a grammar test (either fill-in-the-blank or multiple choice depending on the group), with more mistakes occurring in the grammar test; the more advanced group scored consistently across tasks.…”
Section: Task Variabilitymentioning
confidence: 99%
“…It is known that second language learners of Spanish at the early stages of development have difficulty mastering the preterit and imperfect morphology. The acquisition of past tense and aspect has been studied extensively in research on second language acquisition (cf., Salaberry, 2000;Bardovi-Harlig, 2002;Ayoun & Salaberry, 2005;Bonilla, 2013). This topic is also especially interesting in cross-linguistic studies with learners of various language backgrounds when the learners' native language and target language share different systems in terms of marking tense and aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on the acquisition of the Spanish past tense and aspect has examined different task conditions, including L2 learners' oral and written texts, personal or impersonal narratives, and open-or closedended tasks (see also Bonilla, 2013). However, little research has been conducted to investigate the acquisition of target forms from a corpus-based approach, which is an emerging area of inquiry in Spanish second language acquisition research (Mendikoetxea, 2014).…”
Section: Introductionmentioning
confidence: 99%